(untitled) (World Bulletin of Management and Law, 2023)
The legal sources of Uzbek statehood in the Middle Ages were multifaceted and complex, reflecting the colorful and dynamic nature of the socio-political landscape of the region. The convergence of nomadic traditions, Islamic legal guidelines, and imperial administrative systems created a multifaceted legal framework that provided for the governance and social structure of Uzbek territories. This article is aimed at an in-depth study of these legal sources and their role in the formation of the legal identity of Uzbek statehood in the Middle Ages.